Bernard Malamud's "The lady of the lake": The American Jew as romantic hero? - Maltz, Minna H. (Journal for semitics, 1991)
This paper analyses ""The lady of the lake,"" a story from Malamud's The magic barrel, which presents the problem of Jewish identity within a highly original literary context. The focus of the paper is on the contrast between romance (shown here as illusion) and reality, on the disparity between the way that the protagonist, an American Jew, sees himself and the way that he is presented by the narrator and perceived by the reader. Romance will be considered both as a specific literary genre and in a more general sense in to order to show that, in both instances, Freeman is not the romantic hero he envisions himself to be. On the contrary, he is treated ironically and comically rather than heroically. Within the context of the literary romance, Freeman fails to live up to the prescribed code of honour. Freeman is also depicted as an alienated man who has wasted his life. And finally, he is portrayed as a Jew who denies being Jewish and, by doing so, loses the woman he loves. Freeman's reasons for repudiating his Jewish identity and the contrasting attitudes of the American Jew and the European Jew will be analysed in the conclusion of the paper.